Att ständigt vara tillgänglig - En kvalitativ intervjustudie om ungas uppfattning kring hur användandet av mobiler påverkar relationerna i en familj - Kristensson,Isabell; Thudén,Nora (2024)
Mobile devices have expanded and increased flexibility in communication, but at the same time, they can disrupt presence and create distance and isolation between people. With the help of a qualitative interview study, the purpose of this study is to examine how mobile devices can impact communication and relationships within a family in various ways, based on the perspectives and experiences of young individuals. In summary, our research highlights the need to balance the advantages and disadvantages of technology to strive for the best possible social interaction and family dynamics. Our respondents have expressed a need to stay connected because they want to be available to avoid the feeling of exclusion. Similarly, they articulate that their parents, in various situations, redirect their attention to the screen instead of actively listening and engaging with their children. Consequently, family dynamics and relationships between adolescents and parents are influenced by people's need to stay updated and involved online.
Keywords: mobilephone use; communication; family relationships; adolescent